Corrosion’s impact on wire rope strand response – Comparison with a theoretical predictive model (Fracture and Structural Integrity, 2019)
In this work, we investigate the behavior of wire ropes subject to corrosion damage. The method is based on accelerated corrosion. Decreasing ultimate force and a loss in rigidity was observed from the static tensile tests made on the corroded strands. Otherwise, a predictive model was developed to evaluate the residual ultimate force at a time t in function of the initial diameter, the residual diameter at time t and the ultimate force of the original strand. Thus, experimental and predictive residual force curves are drawn in function of the strand’s fraction of life. From the good correspondence obtained, the proposed method can be applied by engineers to assess the possibility of maintaining structures using wire ropes in service. Indeed, when the applied force on the wire rope approaches its residual bearing force determined by a measure of the residual diameter, the wire rope removal is mandatory.
Keywords: Wire rope; Accelerated corrosion; Damage; Residual force; Reliability; Predictive maintenance